Voluntary information disclosure in company annual reports - C. Firer; G. Meth (South African Journal of Business Management, 1985)
The objective of this study was to measure the level of voluntary disclosure of information by listed South African manufacturing companies. A disclosure index designed to measure such disclosure was constructed. In general a fairly low level of disclosure of non-statutory items was observed in the companies studied. Disclosure tended to improve slightly during the five years 1979-1983. Limited correlation was found between the level of disclosure and firm size.Die doel van hierdie studie was om die vlak van vrywillige openbaarmaking van inligting deur Suid-Afrikaanse vervaardigingsmaatskappye wat op die effektebeurs verskyn, te meet. 'n Indeks om mate van vrywillige openbaarmaking in maatskappyjaarverslae te meet is saamgestel. Oor die algemeen is 'n taamlike lae vlak van openbaarmaking van nie-wetlike items waargeneem in die maatskappye wat bestudeer is. Openbaarmaking het gedurende die vyf jaar 1979-1983 effens verbeter. Beperkte korrelasie is tussen die vlak van openbaarmaking en maatskappygrootte waargeneem.
Keywords: 650